(untitled) (Research, Society and Development, 2020)
Introduction: hardiness can be defined as a strategy for coping with occupational stress and supporting the prevention of Burnout Syndrome. Objective: to analyze the high hardiness scores of nursing professionals at a university hospital. Methodology: observational, cross-sectional and descriptive study, with a quantitative approach, whose sample consisted of 171 nursing professionals in a hospital context, from April to October 2016. For data collection we used the Likert hardiness scale, composed of 30 items, distributed among three dimensions: challenge, commitment and control, ranging from 0 to 90 points. Result: of the 171 participants, there was a predominance of females 136 (79.5%) and an average age of 45 years. In the analysis of the general average of the scores, nurses had a higher average in the commitment (22.4), while in the control, nurses and nursing technicians obtained the same score (21.5). Finally, in the challenge, the nurse scored lower than the other categories (14.3). Conclusion: between the categories of the nursing team, there was a difference in the score of the high scores in the three dimensions of the Hardiness Scale.